Gawat Darurat Medik dan Kesehatan Masyarakat: Literatur Review - Rustandi, Handi; Damayanti, Novita; Alawiyah, Ratu Robiatul; HN, M. Rustam.; Indar, Indar (NHM PRESS, 2024)
Public health emergencies, such as pandemics and natural disasters, have become global challenges that impact various aspects of preparedness, mental health, and health system management. Research shows that mental health support for medical personnel is crucial in reducing stress and burnout which can reduce the effectiveness of services during a crisis. Additionally, efficient communication with the public contributes significantly to increased understanding and compliance with emergency policies. Efficient medical logistics management has proven crucial for timely distribution of aid in the field. There is a need for an integrated approach that combines mental support, logistics and public communication to build a more resilient health system. However, limitations in design, variation in sample size, and measurement methods indicate the need for additional, more comprehensive research